Lidocaine and Ketamine Infusions as Adjunctive Pain Management Therapy: A Retrospective Analysis of Clinical Outcomes in Hospitalized Patients Admitted for Pain Related to Sickle Cell Disease - Zavala, Nicolas A.; Knoebel, Randall W.; Anitescu, Magdalena (Frontiers in Pain Research, 2022)
Objective In this study, we aim to evaluate the efficacy of adjunctive lidocaine and ketamine infusions for opioid reduction in the treatment of sickle cell disease in patients with vaso-occlusive crisis (VOC). Design We retrospectively reviewed a cohort of 330 adult sickle-cell crisis hospital encounters with 68 patients admitted to our institution from July 2017 to August 2018. Methods Upon institutional IRB approval, we obtained initial data from billing records and performed chart reviews to obtain pain scores and confirm total opioid consumption. If provided by the acute pain consultation service, the patients received either a lidocaine or a ketamine infusion of 0.5–2 mg/min or 2–3 mcg/kg, respectively, for a maximum of 24–48 h. We compared the change in opioid consumption before and after infusion therapy to patients that did not receive ketamine or lidocaine. Results Compared to patients that did not receive infusion therapy, ketamine and lidocaine accounted for respective relative decreases of 28 and 23% in average daily morphine consumption (p = 0.02). Patients that received either infusion were 3 to 4 times more likely to decrease their opioid consumption independent of treatment length or baseline opioid doses (p < 0.01). Ketamine and lidocaine therapies were not associated with change in pain scores. When a patient had multiple admissions, opioid reduction was strongly correlated with initiation of infusions in the later visits. Conclusion Both ketamine and lidocaine infusion therapies are effective in reducing opioid consumption for patients with vaso-occlusive crisis. Lidocaine infusion is emerging as an agent for stabilizing opioid doses in VOC for patients with high daily MME.